2022
DOI: 10.1039/d2fo01533a
|View full text |Cite
|
Sign up to set email alerts
|

Anserine beneficial effects in hyperuricemic rats by inhibiting XOD, regulating uric acid transporter and repairing hepatorenal injury

Abstract: This study aimed to investigate the anti-hyperuricemia effect and mechanism of anserine in hyperuricemia rats. Hyperuricemia rat was induced with combination of 750 mg/kgbw·d potassium oxazinate (PO) and 200 mg/kgbw·d...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…When the glomerular filtration function is damaged, the Cr and BUN in the blood cannot be excreted out of the body with urine, resulting in a decrease in the level of Cr and BUN in the blood and the Cr level in the urine [ 36 ]. Therefore, elevated plasma Cr and urea nitrogen and decreased Cr levels in urine are considered to be the main markers of glomerular filtration impairment [ 37 ]. NAG is a highly sensitive indicator of renal tubular function, predominantly found in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…When the glomerular filtration function is damaged, the Cr and BUN in the blood cannot be excreted out of the body with urine, resulting in a decrease in the level of Cr and BUN in the blood and the Cr level in the urine [ 36 ]. Therefore, elevated plasma Cr and urea nitrogen and decreased Cr levels in urine are considered to be the main markers of glomerular filtration impairment [ 37 ]. NAG is a highly sensitive indicator of renal tubular function, predominantly found in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that, in general, bonito, bigeye tuna, and southern tuna contain about 1070 mg, 1260 mg and 636 mg of anserine per 100 g of fish flesh, respectively [ 17 ]. We learned that the doses of anserine used in previous animal experiments ranged from 2 mg/kg·bw to 80 mg/kg·bw [ 18 , 19 ], so we chose the 1 mg/10 mg/100 mg kg·bw as the low/medium/high doses of anserine intervention in our experiment. Our results did show that medium doses of anserine were the most effective in improving hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…The incubation mixtures were prepared by mixing 10 μL of 80 mg/mL sample solution and 90 μL of 0.2, 0.5 and 1.0 U/mL XOD in 100 μL PBS buffer solution to give a final volume of 200 μL 34 . The mixture was incubated for 30 min at 37°C, injected into the UF chamber, and centrifuged at 12,000 × g for 10 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The incubation mixtures were prepared by mixing 10 μL of 80 mg/mL sample solution and 90 μL of 0.2, 0.5 and 1.0 U/mL XOD in 100 μL PBS buffer solution to give a final volume of 200 μL. 34 The mixture was incubated for 30 min at 37 C, injected into the UF chamber, and centrifuged at 12,000 Â g for 10 min at 25 C. The bound ligands were released by adding 200 μL of methanol followed by centrifugation at 12,000 Â g for 10 min; this process was repeated three times. The solvent in the ultrafiltrate was removed under vacuum and redissolved in 50% methanol for HPLC analysis.…”
Section: Screening Xanthine Oxidase Inhibitors and Calculation Of Bon...mentioning
confidence: 99%